Perancangan dan Implementasi Electronic TPM (E-TPM) Berbasis Website dengan QR Code pada Mesin Tire Final Inspection di PT XYZ: [Design and Implementation of a Website-Based Electronic TPM (E-TPM) with QR Codes on The Tire Final Inspection Machine at PT XYZ] - Sialahi, Rudy Vernando; Rachman, Rahardyan (FaST : Jurnal Sains dan Teknologi, 2025)
In the Industrial Revolution 4.0, continuous innovation is crucial for companies striving to achieve their vision and mission. One key initiative is implementing Total Productive Maintenance (TPM). PT XYZ, however, encounters challenge due to its ongoing use of conventional, paper-based methods. These methods have numerous drawbacks, such as incomplete documentation of machine damage, outdated information caused by maintenance department oversights, extended data retrieval times, and the risk of document loss or damage. To overcome these issues, an innovative transition was made from a paper-dependent system to a digital, web-based platform to enhance TPM's effectiveness. Data was collected through direct field observation and processed using the SMART (Specific, Measurable, Achievable, Relevant, Timebound) methodology to accurately identify problems and solutions. A web-based application named E-TPM was developed, utilizing the PHP programming language, the CodeIgniter framework, a MySQL database, and a straightforward, user-friendly interface designed with Bootstrap 5.0. This digital shift offers substantial benefits, including real-time management of machinery damage data, improving TPM monitoring efficiency. Digital data storage reduces the risk of falsification or loss, as information is centrally located. Moreover, E-TPM implementation has led to a significant reduction in paper costs, approximately Rp. 495,000 per year, due to the elimination of paper-based TPM tags that are prone to damage or loss. Finally, access to precise data and in-depth analysis enables management to make better-informed decisions regarding maintenance strategies. Bahasa Indonesia Abstract: Dalam era revolusi industri 4.0, inovasi menjadi kunci bagi perusahaan dalam mencapai visi dan misi mereka. Salah satu inovasi tersebut adalah penerapan Total Productive Maintenance (TPM). Namun, PT XYZ masih mengandalkan sistem konvensional berbasis kertas yang memiliki berbagai kelemahan seperti pencatatan kerusakan mesin yang tidak lengkap, risiko data usang karena pembaruan lambat, pencarian data yang membutuhkan waktu lama, serta risiko kehilangan atau kerusakan dokumen. Sebagai solusi, metode paper-based digantikan dengan sistem digital melalui pengembangan situs web untuk mengoptimalkan TPM. Data dikumpulkan melalui observasi lapangan dan dianalisis menggunakan metode SMART (Specific, Measurable, Achievable, Relevant, Timebound) untuk memastikan solusi yang efektif. Selanjutnya, aplikasi berbasis web yang dinamakan E-TPM dikembangkan menggunakan PHP, dengan framework CodeIgniter, database MySQL, dan desain antarmuka yang mudah digunakan dengan Bootstrap 5.0. Transformasi digital ini memungkinkan pengelolaan data kerusakan mesin secara real-time, meningkatkan efisiensi pengawasan kegiatan TPM. Penyimpanan data secara digital mengurangi risiko pemalsuan dan kehilangan data. Penerapan E-TPM juga berdampak positif pada penghematan biaya hingga Rp 495.000 per tahun dengan mengurangi penggunaan kertas untuk tag TPM. Dengan data yang akurat, manajemen dapat lebih efektif dalam merumuskan strategi pemeliharaan.